2000
DOI: 10.1016/s0194-5998(00)70239-7
|View full text |Cite
|
Sign up to set email alerts
|

Frey's syndrome and parotidectomy flaps: A retrospective cohort study

Abstract: Gustatory sweating, also known as Frey's syndrome, is a recognized phenomenon after parotidectomy. The incidence of clinically significant gustatory sweating may be dependent on the thickness of the skin flap that is elevated at the time of surgery. Dissection in the subcutaneous level or the deeper sub-superficial musculoaponeurotic system level are 2 commonly used techniques in the operation. Twenty-eight patients were prospectively evaluated for Frey's syndrome after superficial parotidectomy. Thirteen pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 9 publications
1
35
1
Order By: Relevance
“…In this paper we found FS positiveness in 21% of the patients who underwent partial parotidectomy, in agreement with literature results that indicate partial parotidectomy as proper treatment for benign parotid tumors 14,15 , and corroborating the already reported surgical approaches to reduce FS, such as rotating the sternocleidomastoid muscle flap 16 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this paper we found FS positiveness in 21% of the patients who underwent partial parotidectomy, in agreement with literature results that indicate partial parotidectomy as proper treatment for benign parotid tumors 14,15 , and corroborating the already reported surgical approaches to reduce FS, such as rotating the sternocleidomastoid muscle flap 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, any approach to the parotid gland where we may have glandular tissue trauma and, consequently trauma to the innervation, may cause FS when we have the regeneration of damaged nerves 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the incidence of subjective Frey's syndrome symptoms in groups I and II was far lower than reported by TAYLOR et al 12 (53%), who had suggested a sub-SMAS flap dissection of the parotidectomy. There was no significant difference found in the incidence of subjective Frey's syndrome between group I and group II or group III and group IV (P = 1.00 and P = 0.83).…”
Section: Discussioncontrasting
confidence: 73%
“…Patients with benign tumours within 3 cm and limited to the superficial lobe may benefit from superficial parotidectomy in order to reduce postoperative facial nerve dysfunction (Witt, 1999) and Frey's syndrome incidence. This syndrome is a common sequel of parotid gland surgery which has been reported with a frequency ranging from 6 to 96% (Dulguerov et al, 1999;Taylor et al, 2000); it is characterized by sweating and flushing of the facial skin over the parotid bed during mastication, often accompanied by discomfort or an ache in the region. It was first described by Duphenix in 1757 in a hunter after a laceration to the parotid, and has also been addressed as ''auriculotemporal syndrome'': Lucja Frey, a Polish neurologist, described a case of gustatory sweating occurring after a bullet injury to the parotid gland (Frey, 1923).…”
Section: Introductionmentioning
confidence: 99%